(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
Studies on sexual dimorphism of gongota Loach Canthophrys gongota (Local name: Pahari Gutum) was performed capturing them from the Atrai River of Dinajpur district in Bangladesh. Females had light blotches and patches with thick and rounded pectoral and pelvic fins while males having dark blotches and patches with thin and comparatively pointed paired fins. Body size, lengths of the anal fin and distances between the bases of pectoral, pelvic and caudal fins were significantly different (5.62 < F < 11.65, P ˂ 0.05) between the sexes of C. gongota. The expansion factors of mean thin-plate grids and vectors also showed that the head region of males was statistically different from females, whereas abdomen and tail of the females were considerably broader than those of the males. Both PCA (principal component analysis) and DFA (discriminant function analysis) plots showed morphologically little overlapping of landmark points which discriminated the females from the males. These findings are the first records on the sexual dimorphism of this rare species that would be baseline in a future study. Bangladesh J. Sci. Ind. Res.54(2), 187-194, 2019